Open financial data from the macedonian stock exchange - Najdenov, Bojan; Pejchinoski, Hristijan; Cieva, Kristina; Jovanovik, Milos; Trajanov, Dimitar (Springer International Publishing, 2014)
The concept of Open Data, which represents the idea that public data should be published in a machine-readable format, starts to take a significant role in modern society. Public data from various fields are being transformed in open data formats and published on systems which allow easier consumption from software agents and applications, as well as the users behind them. On the other hand, people in the business world are trying for a few decades now to establishing standards for financial accounting that govern the preparation of financial reports. Financial reporting has crucial significance for companies today, since it is a record of their work which is presented to their stakeholders and represents a starting point for future business decisions and strategies. In this paper, we use data from the Macedonian Stock Exchange and data from different web sites of Macedonian companies in order to create datasets of Open Financial Data relevant for our country, thus increasing the transparency and improving the data accessibility. We describe the process of transforming the data into 4 star Open Data, and present use-case scenarios which use data from our generated datasets and from the World Bank. The datasets are published and accessible via a SPARQL endpoint, and we demonstrate how a software application can make use of them.
Keywords: Finances, Open Data, Macedonian Stock Exchange, World Bank, RDF, Ontologies